PRIVATE SALES DEEDS IN LAND DISPUTES: WEAKNESSES IN EVIDENCE AND REGISTRATION OBSTACLES - Sulani, Sulani; Darmawan, Didit; Suwito, Suwito; Mardikaningsih, Rahayu; Gautama, Elly Christanty (Gapenas Publisher, 2025)
This normative legal study examines the validity of private deeds of sale and purchase (AJB) and their standing as evidence in land ownership disputes in Indonesia. Utilizing a qualitative literature review, the research analyzes primary regulations including the Civil Code, the Agrarian Law, and the Land Registration Government Regulation. The findings reveal a fundamental legal hierarchy between notarial/PPAT deeds and private deeds. Notarial deeds possess perfect evidentiary strength, executive force, and are the sole legal basis for registering land rights transfer at the Land Office. Conversely, private deeds have only relative evidentiary value, contingent upon signature authentication and corroborating evidence. The legal consequence is severe: transactions based on private deeds cannot be registered, preventing the legal transfer of ownership and leaving the buyer without formal state protection. In court disputes, private deeds are treated as preliminary evidence but are insufficient to establish ownership; judges typically order the creation of a notarial deed or award compensation rather than directly granting property rights. The study concludes that while private deeds may prove the existence of a contractual agreement, they fail to produce the definitive legal effects of notarial deeds, especially concerning land registration and conclusive proof of title. This legal uncertainty underscores the critical importance of formalizing land transactions through authorized officials to ensure security of tenure and prevent protracted disputes.